Social hierarchy and resting metabolic rate in the dwarf cichlid Apistogramma agassizii: the role of habitat enrichment - Kochhann, Daiani; Val, Adalberto Luis (Hydrobiologia, 2017)
Differences in aggressiveness when competing for environmental resources are the main factor leading to social hierarchy in group living fish. Social status acquired is related to changes in physiological parameters, as metabolic rate. Habitat variation can interfere with aggressive behaviour and promote changes in physiological parameters associated with social status. The primary goal of our study was to investigate how differences in habitat complexity affect the relationship between resting metabolic rate (RMR) and social status in the Amazonian dwarf cichlid Apistogramma agassizii. We compared agonistic interactions between pairs of males in aquaria with different habitat enrichment levels, manipulated by adding shelters. RMR was measured before and after hierarchy establishment. Habitat enrichment promotes changes in aggressive behaviour and influences differences in metabolic rate between dominant and subordinate fish. We observed an increase in biting by dominant fish at high enrichment habitat, which could be related to the increase in territory value. We observed an increase in metabolic rate in dominant fish after hierarchy establishment. However, it occurs only in enriched habitats. We concluded that habitat structure interfere with behavioural characteristics in social hierarchies, as aggressiveness, and changes in aggressive interactions affect metabolic rate in different social ranks in the dwarf cichlid Apistogramma agassizii. © 2016, Springer International Publishing Switzerland.
Keywords: Aggression; Agonistic Behavior; Cichlid; Complexity; Habitat Structure; Metabolism; Physiological Response; Apistogramma Agassizii; Apistogramma Reitzigi; Cichlidae